1985
DOI: 10.1159/000146090
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Anatomy and Territories Supplied by the Posterior Gastric Artery

Abstract: The posterior gastric artery, a branch of the splenic artery to the posterior gastric wall, was described for the first time by Walther in 1729. It was often” recognized by many authors since, but consequently ignored by anatomical and surgical textbooks until its rediscovery and description by Suzuki et al. [Ann. Surg. 187:134–136, 1978]. The incidence of the posterior gastric artery differs between 4 and nearly 100%. All authors describe posterior gastric regions being supplied by the posterior gastric arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 5 publications
0
14
1
Order By: Relevance
“…Its observed prevalence in humans varies with the method employed for its detection. In anatomic series it varies from 4 to 99% [31]. In angiographic studies its prevalence is lower on average, from 36.8 according to Kupic et al [13] to 46% as reported by Di Dio et al [5].…”
Section: Pancreatic Neck a (Or Dorsal Pancreatic A Or Posterior Panmentioning
confidence: 95%
See 4 more Smart Citations
“…Its observed prevalence in humans varies with the method employed for its detection. In anatomic series it varies from 4 to 99% [31]. In angiographic studies its prevalence is lower on average, from 36.8 according to Kupic et al [13] to 46% as reported by Di Dio et al [5].…”
Section: Pancreatic Neck a (Or Dorsal Pancreatic A Or Posterior Panmentioning
confidence: 95%
“…First described by Walther in 1729 [36] and so called by Haller in 1745 [9,31], it arises from the splenic a. trunk. Its observed prevalence in humans varies with the method employed for its detection.…”
Section: Pancreatic Neck a (Or Dorsal Pancreatic A Or Posterior Panmentioning
confidence: 99%
See 3 more Smart Citations